Acute Myeloid Leukemia in a Cholecystectomy Specimen. (26th September 2022) - Hernandez Caballero, Ana I.; Castro-Echeverry, Eduardo; Katerji, Roula; Gonzalez, Christopher
Abstract : A 76-year-old man was admitted into the ER for upper abdominal pain. Physical exam and CT scan confirmed acute cholecystitis with multiple cholelithis, and a cholecystectomy was performed. The cholecystectomy specimen showed chronic cholecystitis with exuberant inflammatory infiltrate. On careful examination of the specimen, large atypical cells with vesicular chromatin, folded nuclei, and inconspicuous red nucleoli were noted percolating into the gallbladder wall and lining vascular spaces. These cells were positive for CD117, CD43, and myeloperoxidase and negative for CD20 and CD3 stains. Further workup including peripheral blood flow cytometry confirmed a population of circulating immature myeloid precursors comprising about 38% of events. This is a rare case of acute myeloid leukemia that came to clinical attention by incidentally involving the gallbladder.